Dithioesterified cellulose nanofiber

JP7636195B2Active Publication Date: 2025-02-26RENGO CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021021788
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-14
Filing Date
2021-02-15
Publication Date
2025-02-26
Estimated Expiration
2041-02-15

AI Technical Summary

Benefits of technology

【0014】 この発明により得られるジチオエステル化セルロースナノファイバーは、ザンテート化セルロースナノファイバーに比べて熱安定性が向上しており、製造後に保管して時間を置いてから樹脂やゴムに添加する場合でも有用に用いることができる。また、末端が-OCSS-M+のイオンとなっているザンテート基に比べて、-OCSSR基であるジチオエステル基は疎水性が高いため、樹脂やゴム中に添加した際に親和性が高く、混練しやすくなるので、樹脂組成物中に均一に分散して、品質を向上させることができる。さらに、酸性溶液中での安定性もザンテート化セルロースナノファイバーに比べて向上しており、樹脂やゴムなどの添加剤などとして広く用いられる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636195000012
    Figure 0007636195000012
  • Figure 0007636195000013
    Figure 0007636195000013
  • Figure 0007636195000014
    Figure 0007636195000014
Patent Text Reader

Abstract

To provide a nanofiber having improved heat stability and dispersibility in resin and rubber, in order to make the most of beneficial properties of xanthate-based cellulose nanofiber.SOLUTION: The present disclosure provides a dithioester-based cellulose nanofiber, which is a nanofiber having a cellulose skeleton, wherein, any of hydroxy groups included in cellulose is replaced with a dithioester group represented by -OCSSR.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a modified xanthated cellulose nanofiber. [Background technology]

[0002] It has long been known that cellulose has a reinforcing effect on resins and rubbers (Patent Document 1). However, since typical fine powder cellulose fibers are in the form of particles made by cutting the fibers, it is difficult to expect a high reinforcing effect that utilizes the network of fine cellulose fibers.

[0003] A new material called nanocellulose, which is made by breaking down plant-derived cellulose materials to the nano level, has been attracting attention. Among these, materials in which the fibers in cellulose are finely loosened to a fiber diameter of about 3 to 100 nm have a large specific surface area and excellent properties as reinforcing fibers, so research and development of this material is being actively carried out. Various names have been proposed for this material, but in this application, this material is called cellulose nanofiber. To produce this cellulose nanofiber, it is necessary to finely defibrate cellulose materials such as pulp, but even if you try to defibrate the cellulose material itself as it is, it requires a lot of energy because the fibers are bound to each other by strong hydrogen bonds. For this reason, a technology has been proposed to make it easier to obtain cellulose nanofibers by chemically denaturing the cellulose material to make it easier to defibrate it.

[0004] Examples of cellulose nanofibers obtained by such chemical modification include the following: TEMPO-oxidized cellulose nanofibers, which are made by introducing carboxyl groups into cellulose using 2,2,6,6-tetramethyl-1-piperidine-N-oxy radical (hereinafter referred to as "TEMPO") as a catalyst to defibrate it; and TEMPO-oxidized cellulose nanofibers, which are made by adding carbon disulfide to alkali-treated cellulose to form xanthate groups (-OCSS). - M + Examples of such nanofibers include xanthate-modified cellulose nanofibers in which a phosphate group has been introduced, and phosphate-modified cellulose nanofibers in which a phosphate group has been introduced.

[0005] In particular, it has been reported in Patent Document 2 that xanthate cellulose nanofibers can provide a high reinforcing effect when introduced into resins or rubbers. In particular, in rubber, it is believed that in addition to the reinforcing effect of the nanofibers, the sulfur contained in the xanthate group also exerts a vulcanization-accelerating effect. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2005-75856 A [Patent Document 2] International Publication WO2018 / 235912A1 Summary of the Invention [Problem to be solved by the invention]

[0007] However, since xanthate-modified cellulose nanofibers have poor thermal stability, some of the xanthate groups are easily detached even at room temperature, which causes problems with storage. In addition, although cellulose itself is hydrophilic, the introduction of the xanthate groups makes the xanthate-modified cellulose nanofibers more hydrophilic, making them difficult to mix with hydrophobic resins and rubbers when kneaded, resulting in an uneven dispersion state, which means that the reinforcing effect of the cellulose nanofibers cannot be fully demonstrated.

[0008] Therefore, the object of the present invention is to obtain nanofibers having improved thermal stability and dispersibility in resins and rubbers in order to utilize the useful properties of xanthated cellulose nanofibers. [Means for solving the problem]

[0009] The present invention solves the above-mentioned problems by providing a cellulose nanofiber, which is a nanofiber having a cellulose skeleton in its molecular structure, in which hydroxyl groups in cellulose are substituted with dithioester groups represented by the following formula (1) in place of one of the hydroxyl groups.

[0010] -OCSSR (1) (R is a hydrocarbon group having 1 to 12 carbon atoms)

[0011] Specifically, an embodiment can employ a dithioesterified cellulose nanofiber having a degree of substitution, which is the average number of hydroxyl groups substituted with the dithioester group per glucose unit constituting the cellulose backbone, of 0.1 or more and 0.4 or less, and an average fiber diameter of 3 nm or more and 250 nm or less.

[0012] The dithioesterified cellulose nanofibers according to the present invention can be produced by adding a halogenated hydrocarbon to an aqueous suspension of xanthated cellulose nanofibers and reacting it with the xanthate groups.

[0013] A resin composition in which the dithioesterified cellulose nanofiber according to the present invention is incorporated into a resin or rubber is useful as a resin composition with improved strength. Effect of the Invention

[0014] The dithioesterified cellulose nanofibers obtained by this invention have improved thermal stability compared to xanthated cellulose nanofibers, and can be usefully used even when they are stored after production and then added to resins or rubbers after a period of time. - M +Compared to the xanthate group, which is an ion, the dithioester group, which is an -OCSSR group, is highly hydrophobic, so when added to resins or rubbers, it has a high affinity and is easy to knead, so it can be uniformly dispersed in the resin composition and improve quality. Furthermore, its stability in acidic solutions is also improved compared to xanthate cellulose nanofibers, and it is widely used as an additive for resins, rubbers, etc. [Brief description of the drawings]

[0015] [Figure 1] A graph comparing the stress-strain curves of Experimental Examples 1-1 and 1-2 and Comparative Experimental Examples 1-1 and 1-2 [Diagram 2] A graph comparing the stress-strain curves of Experimental Examples 1-1 and 1-3 and Comparative Experimental Examples 1-1 and 1-2 [Diagram 3] A graph comparing the stress-strain curves of Experimental Examples 1-1, 1-4, 1-5, and Comparative Experiment 1-1 [Figure 4] A graph comparing the stress-strain curves of Experimental Example 1-6 and Experimental Comparison Examples 1-3 and 1-4. [Diagram 5] A graph comparing the stress-strain curves of Experimental Examples 1-1 and 1-7 and Comparative Experimental Examples 1-1, 1-5, and 1-6 [Figure 6] A graph comparing the stress-strain curves of Experimental Examples 2-1 and 2-2 and Comparative Experimental Examples 2-1 and 2-2 [Figure 7] Graph comparing stress-strain curves of Experimental Example 3-1 and Experimental Comparison Examples 3-1 and 3-2 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention relates to a dithioesterified cellulose nanofiber having a dithioester group, a method for producing the same, and a resin composition containing the dithioesterified cellulose nanofiber.

[0017] The dithioesterified cellulose nanofiber according to the present invention is a cellulose nanofiber having a cellulose skeleton in which glucose units are linked as a basic structure. If the basic structure is a cellulose skeleton, not all of the constituent units are glucose, and it also includes those in which some of the terminal groups are modified and those in which some of the structures are changed.

[0018] The dithioesterified cellulose nanofiber according to the present invention is a modified compound having a dithioester group in which a hydroxyl group is substituted for any of the hydroxyl groups of the glucose units of the cellulose skeleton. Cellulose has three hydroxyl groups per glucose unit constituting it, and it is preferable that an average of 0.1 or more hydroxyl groups per glucose unit are substituted with a dithioester group. Hereinafter, the average number of hydroxyl groups substituted with a dithioester group per glucose unit is referred to as the degree of substitution. If the degree of substitution is less than 0.1, the hydrophobicity improving effect and vulcanization accelerating effect of the dithioester group are insufficient, and the advantages compared to unsubstituted cellulose nanofibers are not sufficient. Basically, the higher the degree of substitution, the more preferable it is from the viewpoint of reinforcing effect, but in terms of production, it is not preferable for the degree of substitution to exceed 0.4. If the degree of substitution exceeds 0.4, there is a risk that the xanthate cellulose nanofiber, which is the raw material of the dithioesterified cellulose nanofiber, will dissolve in water as a dispersion medium during defibration treatment when producing the xanthate cellulose nanofiber.

[0019] The dithioester group has a structure of the following formula (1). R is a hydrocarbon group having 1 to 12 carbon atoms. Specific examples of R include linear alkyl groups such as butyl and octyl groups, aromatic alkyl groups such as benzyl groups, and alkenyl groups such as vinyl and allyl groups. R may be a saturated or unsaturated hydrocarbon group. R is not limited to linear groups. From the viewpoint of ease of dissolving in water, R preferably has 8 or less carbon atoms, and from the viewpoint of ease of reaction, R having 4 or less carbon atoms is more preferable.

[0020] -OCSSR (1)

[0021] The dithioesterified cellulose nanofiber according to the present invention preferably has an average fiber diameter of 3 nm or more, and more preferably 5 nm or more. Since the fiber diameter of microfibrils, which are the constituent units of natural cellulose, is 2 to 3 nm in higher plants, a large amount of energy is required for defibration to make it less than 3 nm, and there is a risk of high production costs. On the other hand, a diameter of 250 nm or less is preferable, and a diameter of 200 nm or less is more preferable. When nanofibers that are too thick due to insufficient defibration are included in a resin composition, it is difficult to form a network structure of nanofibers, and there is a risk of the reinforcing effect not being fully exhibited.

[0022] The dithioesterified cellulose nanofibers according to the present invention can be produced, for example, by adding a halogenated hydrocarbon to an aqueous suspension of xanthated cellulose nanofibers and reacting with the xanthate group. The dispersion medium of this aqueous suspension may be water alone, or a liquid in which a polar solvent other than water is mixed with water to facilitate dissolving the halogenated hydrocarbon during the reaction may be used. As these polar solvents, for example, dimethyl sulfoxide (DMSO) or N,N-dimethylformamide (DMF) can be used. In addition, an emulsifying aid may be added to uniformly disperse the halogenated hydrocarbon in the aqueous dispersion medium. This is because the halogenated hydrocarbon is hydrophobic and is difficult to disperse in the aqueous suspension as it is.

[0023] The aqueous suspension of xanthated cellulose nanofibers may be prepared by using the dispersion liquid obtained after defibrating the xanthated cellulose as it is, or by dispersing the xanthated cellulose nanofibers once dried in a dispersion medium again. The xanthated cellulose used for defibration usually contains Na as a cation. + However, it may be ion-exchanged to have a different cation.

[0024] In the above halogenated hydrocarbon, Cl, Br, or I can be suitably used as the halogen. The hydrocarbon group of the above halogenated hydrocarbon is a functional group corresponding to R in the above dithioester group. That is, examples of the functional group include linear alkyl groups such as butyl and octyl groups, aromatic alkyl groups such as benzyl groups, and alkenyl groups such as vinyl and allyl groups.

[0025] It should be noted that the production method is not limited to the method using the above-mentioned esterification reaction, so long as dithioesterified cellulose nanofibers having dithioester groups can be obtained.

[0026] The dithioesterified cellulose nanofiber according to the present invention is preferably effective in improving the strength of a resin composition by being incorporated into a resin or rubber and used as such. In particular, when the dithioesterified cellulose nanofiber is incorporated into a resin composition using rubber such as natural rubber or synthetic rubber as the resin, not only the strength of the nanofiber is improved, but also the sulfur possessed by the dithioester group promotes vulcanization. The method of adding the resin composition is not particularly limited. For example, the dithioesterified cellulose nanofiber may be added during kneading of the resin composition, kneaded, and then curing, vulcanization, or the like may be performed.

[0027] The above resin composition may contain additives such as vulcanization accelerators, vulcanizing agents, antiaging agents, fillers, waxes, reinforcing agents, softeners, bulking agents, colorants, flame retardants, lubricants, plasticizers, and other additives other than the dithioesterified cellulose nanofibers, depending on the application. Examples of fillers include carbon black, silica, calcium carbonate, and the like. Examples of vulcanizing agents for rubber include sulfur content that is added separately. EXAMPLES

[0028] The following describes specific examples of the present invention. First, as a preliminary step to obtaining dithioesterified cellulose nanofibers, we will explain the manufacturing procedure for obtaining the raw material xanthated cellulose nanofibers and the method for measuring the physical properties of the xanthated cellulose nanofibers. Note that cellulose nanofibers are sometimes abbreviated as "CNF". The following materials were used. Kraft pulp (manufactured by Nippon Paper Industries Co., Ltd.: NBKP, α-cellulose content: 90% by mass, average degree of polymerization of α-cellulose: 1000) hereinafter referred to as "NBKP".

[0029] (Example 1: Dithioesterified CNF Allyl) <Alkaline treatment: Preparation of dithioesterified CNF 1> NBKP was weighed out so that the pulp solid content (pulp solid content is the content excluding the water content in the pulp; the same applies below) was 1 kg. 25 kg of an 8.5 mass% aqueous sodium hydroxide solution was added to this NBKP, and the mixture was stirred at room temperature for 3 hours to perform an alkali treatment. The pulp after this alkali treatment was subjected to solid-liquid separation using a centrifugal dehydrator (Kokusan Co., Ltd., H-130C, filter cloth 400 mesh) to obtain a dehydrated alkali cellulose. The sodium hydroxide content of this dehydrated alkali cellulose was 7.5 mass%, and the pulp solid content was 27.4 mass%.

[0030] <Xanthate treatment: Preparation of dithioesterified CNF 2> The dehydrated alkali cellulose prepared above was weighed to have a pulp solid content of 300 g. 105 g of carbon disulfide (35% by mass relative to the pulp solid content) was added to the dehydrated product, and the sulfurization reaction was allowed to proceed at room temperature for 4.5 hours to perform a xanthate treatment, thereby obtaining xanthated cellulose.

[0031] <Xanthate Substitution Degree Measurement> The degree of xanthate substitution of the xanthated cellulose was measured by the Bredee method and found to be 0.312. The degree of xanthate substitution is the average number of hydroxyl groups substituted with xanthate groups per glucose unit of cellulose. The measurement of the degree of xanthate substitution by the Bredee method was carried out as follows. 1.5 g of xanthated cellulose was weighed as a solid content, and 40 mL of saturated ammonium chloride aqueous solution cooled to 5 ° C was added. The xanthated cellulose sample was crushed with a glass rod and mixed well, and then left for 15 minutes, filtered with GFP filter paper (GS-25 manufactured by ADVANTEC), and thoroughly washed with saturated ammonium chloride aqueous solution. 50 mL of 0.5 mol / L sodium hydroxide aqueous solution cooled to 5 ° C was added to the sample remaining on the GFP filter paper, and the GFP filter paper was stirred. The stirred liquid was left for 15 minutes, and then neutralized with 1.5 mol / L acetic acid aqueous solution. Phenolphthalein indicator was used as the indicator. After neutralization, 250 mL of distilled water was added and thoroughly stirred, and 10 mL of 1.5 mol / L acetic acid aqueous solution and 10 mL of 0.05 mol / L iodine aqueous solution were added. This solution was titrated with 0.05 mol / L sodium thiosulfate aqueous solution. A 1% by mass starch aqueous solution was used as an indicator. The degree of xanthate substitution was calculated from the following formula (1) based on the titration amount of sodium thiosulfate aqueous solution and the cellulose content in the sample. The cellulose content in the xanthated cellulose sample was determined by adding water to the xanthated cellulose to disperse it, adding hydrochloric acid to perform a regeneration treatment, filtering the cellulose after the regeneration treatment, thoroughly washing it, and then drying it to measure the mass of only the cellulose.

[0032] Xanthate substitution degree = (0.05 × 10 × 2 - 0.05 × sodium thiosulfate titration (mL)) ÷ 1000 ÷ (cellulose content in sample (g) / 162.1) ... (1)

[0033] <Defibrillation process: Preparation of dithioesterified CNF 3> The xanthated cellulose produced by the above xanthation treatment was weighed out so that the solid content was 300 g, and distilled water was added so that the solid content concentration was 5% by mass, and the mixture was stirred and dispersed with a stirrer. The dispersion was centrifuged using the centrifugal dehydrator, and distilled water was added to thoroughly wash the dispersion to remove impurities, alkali, unreacted carbon disulfide, etc. All of the washed xanthated cellulose was collected, and distilled water was added to make a 60 kg aqueous suspension with a cellulose content concentration (hereinafter referred to as "cellulose concentration") of 0.5% by mass. This aqueous suspension was defibrated by passing it five times using a high-pressure homogenizer (manufactured by Sanwa Engineering Co., Ltd., H20 type) at a flow rate of 2.5 L / min and a pressure of 40 MPa to obtain xanthated CNF. The degree of xanthate substitution of the obtained xanthated CNF was 0.294.

[0034] <Degree of defibration of xanthate CNF> Distilled water was added to the aqueous suspension of the xanthated CNF (cellulose concentration 0.5% by mass) to dilute the cellulose concentration to 0.1% by mass. This diluted aqueous suspension was centrifuged at 12000G for 10 minutes using a centrifuge (Avanti J-25I, manufactured by Beckman Coulter) to settle the undefibrated material. The supernatant was separated, and distilled water was added to the settled undefibrated material and centrifuged again to wash the undefibrated material. The undefibrated material was transferred to a crucible and completely dried, and the mass of the undefibrated material was measured. The production rate of nanofibers was calculated from the mass of the undefibrated material and the cellulose content in the xanthated cellulose using the following formula (2), which was 99.0% by mass.

[0035] Nanofiber production rate (mass%) = (cellulose content in xanthate cellulose - mass of undefibrated material) ÷ ​​(cellulose content in xanthate cellulose) × 100 ... (2)

[0036] <Measurement of fiber diameter of xanthate-modified CNF> A water suspension of xanthate-modified CNF diluted with water to a cellulose concentration of 0.1% by mass was placed in a centrifuge tube, and centrifuged at 12000G for 10 minutes using the centrifuge to collect the centrifugal supernatant. This centrifugal supernatant was further diluted with distilled water, applied to a support film, stained with uranyl acetate, and dried on the support film to obtain a dried specimen. The dried specimen was observed at an accelerating voltage of 120 kV using a transmission electron microscope (TEM: JEM-1400, manufactured by JEOL Ltd.). 50 nanofibers were selected from the 50,000x image thus obtained, and the fiber diameter was measured. The fiber diameter was in the range of 3.0 nm to 7.4 nm, and the average fiber diameter, which was the average of the measured values, was 6.1 nm.

[0037] <Measurement of sulfur content of xanthate-modified CNF> The aqueous suspension of xanthate-modified CNF (cellulose content 0.5% by mass) obtained by the same procedure as the above defibration process was freeze-dried to obtain a freeze-dried product of xanthate-modified CNF. The sulfur content of this freeze-dried product was measured using a chlorine / sulfur analyzer (TOX-2100H, manufactured by Mitsubishi Chemical Analytech Co., Ltd.). The sulfur content in the xanthate-modified CNF was 8.7% by mass.

[0038] <Dithioesterification and redispersion: Part 4 of the preparation of dithioesterified CNF> Distilled water was added to 5 kg of an aqueous suspension of xanthate-modified CNF (cellulose content 0.5% by mass) obtained by the same procedure as above up to the defibration treatment, and the concentration was diluted to 0.25% by mass, and neutralized with 1.5 mol / L acetic acid. After neutralization, the mixture was stirred in a 0°C water bath for 1 hour, and when the liquid temperature reached 5°C or below, 55 g of allyl bromide (Tokyo Chemical Industry Co., Ltd.) was added, and the mixture was stirred for 12 hours while maintaining the liquid temperature at 5°C or below to perform a dithioesterification treatment, producing a dithioesterified CNF having an allyl group (hereinafter sometimes referred to as "allyl dithioesterified CNF").

[0039] The aqueous suspension of the xanthate-modified CNF (the dithioesterified CNF according to the present invention) after the dithioesterification treatment was thoroughly washed by adding ethanol and distilled water while centrifuging using the centrifugal dehydrator. All the washed dithioesterified CNF was collected, and distilled water was added to prepare 10 kg of aqueous suspension with a dithioesterified CNF content of 1 mass%. This aqueous suspension was redispersed by passing it twice using a high-pressure homogenizer (manufactured by Sanwa Engineering Co., Ltd., H20 type) at a flow rate of 2.5 L / min and a pressure of 40 MPa. After the redispersion treatment, a micrograph of the redispersed dithioesterified CNF was taken to measure the fiber diameter, which was in the range of 3.2 nm to 7.4 nm and the average fiber diameter was 6.1 nm. The sulfur content was also measured and found to be 8.6 mass%. As described above, the sulfur content of the xanthate-modified CNF before modification was 8.7% by mass, so it was confirmed that the dithioesterification treatment modified the xanthate groups but hardly eliminated them, and maintained the degree of substitution.

[0040] (Example 2: Dithioesterified CNF·allyl with varying degrees of substitution) In order to obtain allyl dithioesterified CNF with different degrees of substitution, in the "xanthation treatment: dithioesterified CNF preparation 2" step of the preparation process of the precursor xanthated CNF, the dehydrated alkali cellulose was changed to 100 g of pulp solids and the amount of carbon disulfide added was changed to 24 g (24 mass% relative to pulp solids), and the same operation was performed to obtain xanthated CNF with different degrees of substitution. The fiber diameter of the obtained xanthated CNF was 3.2 to 14.5 nm, the average fiber diameter was 10.3 nm, the degree of substitution was 0.204, and the sulfur content was 6.3 mass%.

[0041] Using the aqueous suspensions of xanthate-modified CNFs with different degrees of substitution, the same operations as in "Dithioesterification and redispersion treatment: Preparation of dithioesterified CNFs" were carried out to obtain allyldithioesterified CNFs with different degrees of substitution. The fiber diameters of the obtained allyldithioesterified CNFs were 3.1 to 14.9 nm, the average fiber diameter was 11.1 nm, and the sulfur content was 6.3%.

[0042] (Example 3: Ester group modification - butyl) In the dithioesterification treatment of Example 1, allyl bromide was changed to 62.5 g of butyl bromide (manufactured by Tokyo Chemical Industry Co., Ltd.), and allyl dithioester was changed to butyl dithioester. Otherwise, butyl dithioesterified CNF was produced by the same procedure as in Example 1. The fiber diameter of the obtained butyl dithioesterified CNF was 3.1 to 7.2 nm, the average fiber diameter was 6.0 nm, and the sulfur content was 8.3%.

[0043] (Example 4: Ester group modification - octyl) In the dithioesterification treatment of Example 1, allyl bromide was changed to 87.5 g of octyl bromide (manufactured by Tokyo Chemical Industry Co., Ltd.), and allyl dithioester was changed to octyl dithioester. Except for this, octyl dithioesterified CNF was produced by the same procedure as in Example 1. The fiber diameter of the obtained octyl dithioesterified CNF was 3.2 to 7.7 nm, the average fiber diameter was 6.2 nm, and the sulfur content was 8.1%.

[0044] <Evaluation of physical properties based on the degree of substitution> (Comparative Example 1: Increase in Substitution Degree) Among the steps of producing the precursor xanthate-modified CNF in Example 1, in <Xanthate-modified treatment: 2. Preparation of dithioesterified CNF>, the dehydrated alkali cellulose was changed to 100 g of pulp solids, and the amount of carbon disulfide added was changed to 70 g (70% by mass relative to the pulp solids), and the same operation was performed to obtain xanthate-modified cellulose with different degrees of xanthate substitution. The degree of xanthate substitution of the obtained xanthate-modified cellulose was 0.412. When the same operation as in <Defibrillation treatment: 3. Preparation of dithioesterified CNF> was performed using 100 g of this xanthate-modified cellulose, the amount of xanthate-modified CNF recovered after washing was 19.2 g, and most of it dissolved during washing. For this reason, it was found that if dithioesterified CNF is produced using xanthate-modified CNF with a high degree of xanthate substitution, the production itself is possible, but the production efficiency is significantly deteriorated.

[0045] <Confirmation of thermal stability of dithioesterified CNF> Distilled water was added to the allyl dithioesterified CNF aqueous suspension (dithioesterified CNF content 1% by mass, sulfur content 8.6% by mass) prepared in Example 1 to dilute the dithioesterified CNF content to 0.5% by mass. 100 g of this diluted aqueous suspension was taken out and placed in a plastic container and stored in a box-type dryer at 30 ° C. The sulfur content was measured before the start of storage (0 hours), and after 18 hours, 24 hours, 48 ​​hours, 72 hours, and 144 hours from the start of storage. In addition, the same operation was performed on a xanthate-treated CNF aqueous suspension (CNF concentration 1% by mass, sulfur content 8.7% by mass) that was not subjected to dithioesterification treatment for comparison. The results are shown in Table 1.

[0046] [Table 1]

[0047] (Consideration) In the case of xanthate-modified CNF that was not subjected to dithioesterification treatment, the sulfur content tended to decrease over time, but in the case of allyl dithioesterified CNF, the sulfur content remained almost constant. This shows that by subjecting xanthate-modified CNF to dithioesterification treatment, the -CSS- group is less likely to be eliminated even when heated, improving its thermal stability.

[0048] <Confirmation of the stability of dithioesterified CNF in acid solution> Distilled water was added to the allyl dithioesterified CNF aqueous suspension (dithioesterified CNF content 1% by mass, sulfur content 8.6% by mass) prepared in Example 1 to dilute the dithioesterified CNF content to 0.5% by mass. Formic acid was added to this diluted aqueous suspension to adjust the pH of the aqueous suspension to 4, and the suspension was allowed to stand at room temperature. The sulfur content was measured in the same manner as in the case of the xanthated CNF described above immediately after the start of standing (0 hours), and after 1 hour, 2 hours, 4 hours, and 6 hours from the start of standing. In addition, the same operation was performed on a xanthated CNF aqueous suspension (CNF concentration 1% by mass, sulfur content 8.7% by mass) that was not subjected to dithioesterification treatment for comparison. The results are shown in Table 2.

[0049] [Table 2]

[0050] (Consideration) In the case of xanthate-modified CNF that was not subjected to dithioesterification treatment, the sulfur content tended to decrease with time, but in the case of allyl dithioesterified CNF (Example 1), the sulfur content remained almost constant over time. From this, it was found that by subjecting xanthate-modified CNF to dithioesterification treatment, the -CSS- group is less likely to be eliminated even when it comes into contact with formic acid, and stability is improved even when the pH is low.

[0051] Below is an experimental example in which the dithioesterified CNF prepared in the examples was added to a resin. <1. Confirmation of the effect of increasing the strength of natural rubber sheets by mixing with natural rubber latex> (Comparison by degree of substitution) (Experimental Example 1-1) - Preparation of master batches by heat solidification The allyl dithioesterified CNF aqueous suspension (dithioesterified CNF content 1% by mass) prepared in Example 1 was mixed with natural rubber (hereinafter abbreviated as "NR") latex (HA NR LATEX manufactured by Resitex Co., Ltd., solid content 60% by mass, ammonia 0.7% by mass), and 14% by mass ammonia water. The dithioesterified CNF content was 5 parts by mass per 100 parts by mass of NR solid content. The mixture was stirred and mixed at 8000 rpm for 5 minutes using a rotary homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., AM-7). The slurry after stirring and mixing was left to dry at 70 ° C for 2 days, and then dried under reduced pressure to prepare an NR master batch.

[0052] - Preparation of compound sheets and vulcanized rubber sheets 300 g of the NR master batch prepared above was masticated using a two-roll machine (a φ200 mm × L500 mm mixing roll machine manufactured by Nippon Roll Manufacturing Co., Ltd.) heated to 50° C. Next, 1.5 g of stearic acid (manufactured by Nacalai Tesque Co., Ltd.), 18 g of zinc oxide (manufactured by Nacalai Tesque Co., Ltd.), 10.5 g of sulfur (manufactured by Nacalai Tesque Co., Ltd.), and 2.1 g of a vulcanization accelerator (Suncerer NS-G manufactured by Sanshin Chemical Industry Co., Ltd.) were added and mixed to prepare a compound sheet having a thickness of 2 mm or more.

[0053] The 90% vulcanization time (Tc90) of the obtained compound sheet was measured by a vulcanization judger (Curastometer V type, manufactured by Orintec Co., Ltd., measuring temperature 150° C., measuring time 20 minutes), and the Tc90 was 6.6 minutes.

[0054] The obtained compound sheet was placed in a mold and compression molded at 150°C for 6.6 minutes based on the measured Tc90 value to produce a vulcanized rubber sheet with a thickness of 2 mm.

[0055] Strength property measurement From the obtained vulcanized rubber sheet, test pieces were punched out in the shape of a JIS No. 3 dumbbell (n=5), and the thickness of each test piece was measured using a film thickness measuring instrument dial gauge 0.001 mm (Ozaki Seisakusho Co., Ltd.) (n=3). The test pieces were subjected to a tensile test (gripping width: 50 mm, speed: 500 mm / min JIS K6251 compliant: corresponding to ISO37) using a tensile tester (Shimadzu Corporation Precision Universal Tester AG-1000D) to determine the tensile stress and elongation. The results are shown in Table 3. Note that phr indicates the mass parts (addition amount) of CNF added to 100 mass parts of rubber, M100 indicates the tensile stress at 100% elongation, M300 indicates the tensile stress at 300% elongation, and M500 indicates the tensile stress at 500% elongation.

[0056] (Experimental Example 1-2) Using the allyldithioesterified CNF with different degrees of substitution prepared in Example 2, the "Preparation of master batch by heat coagulation", "Preparation of compound sheet and vulcanized rubber sheet", and "Measurement of strength properties" of Experimental Example 1-1 were performed in the same manner. The results are shown in Table 3.

[0057] (Experimental Comparative Example 1-1) In the "Preparation of Masterbatch by Heat Coagulation" of Experimental Example 1-1, a vulcanized rubber sheet was prepared in the same manner as above, except that dithioesterified CNF was not added, and strength properties were measured. The results are shown in Table 3. Tc90 was 8.0 minutes.

[0058] (Experimental Comparative Example 1-2) In the "Preparation of Masterbatch by Heat Coagulation" of Experimental Example 1-1, a rubber sheet was prepared in the same manner as above, except that xanthate-modified CNF was used instead of dithioesterified CNF, and strength properties were measured. The results are shown in Table 3. Tc90 was 5.4 minutes.

[0059] [Table 3]

[0060] (Consideration) FIG. 1 shows a graph of stress-strain curves with strain (=elongation) on the horizontal axis and stress on the vertical axis for Experimental Examples 1-1 and 1-2 and Experimental Comparative Examples 1-1 and 1-2. The stress at the same strain was improved by the addition of both xanthate-modified CNF and dithioesterified CNF, but the dithioesterified CNF showed a higher value than the xanthate-modified CNF, and it was confirmed that the strength improvement effect of the dithioesterified CNF was higher. In addition, a comparison of dithioesterified CNFs with different degrees of substitution showed that Experimental Example 1-1, which has a high degree of substitution of about 0.3, had a higher strength improvement effect than Experimental Example 1-2, which has a degree of substitution of about 0.2. Furthermore, it was confirmed that the Tc90 of the dithioesterified CNF (Experimental Example 1-1) was not significantly changed compared to the xanthate-modified CNF (Experimental Comparative Example 1-2), and the vulcanization acceleration effect was maintained.

[0061] (Evaluation of physical properties regarding differences in additive amounts) (Experimental Example 1-3: Increased amount added) In the "Preparation of master batch by heat solidification" step of Experimental Example 1-1, the amount of dithioesterified CNF was increased so that the content of dithioesterified CNF of Example 1 was 5 to 10 parts by mass (10 phr) per 100 parts by mass of NR solid content. A vulcanized rubber sheet was produced in the same manner as in Experimental Example 1-1 except for the above. Tc90 was 7.3 minutes.

[0062] The above strength property measurements were also performed on Experimental Example 1-3, and the stress at break and elongation (= strain) were obtained. The results were compared between Experimental Example 1-1 (allyl dithioesterified CNF added amount 5 phr) and Experimental Example 1-3 (allyl dithioesterified CNF added amount 10 phr), and are shown in Table 4 and Figure 2 together with Experimental Comparative Example 1-1 (no addition) and Experimental Comparative Example 1-2 (xanthate-modified CNF) for reference. Note that M30 indicates the tensile stress at 30% elongation, M100 indicates the tensile stress at 100% elongation, and M300 indicates the tensile stress at 300% elongation. When the amount of dithioesterified CNF added was changed, it was shown that Experimental Example 1-3, which had a large amount added, generally had a higher strength improvement effect than Experimental Example 1-1, which had a small amount added.

[0063] [Table 4]

[0064] (Evaluation of changes in ester groups) (Experimental Example 1-4: Ester group change - butyl) In the "Preparation of Masterbatch by Heat Coagulation" of Experimental Example 1-1, a rubber sheet was prepared in the same manner as above, except that the butyl dithioesterified CNF prepared in Example 3 was used instead of the allyl dithioesterified CNF, and strength properties were measured. Tc90 was 7.0 minutes.

[0065] (Experimental Example 1-5: Ester group change - octyl) In the "Preparation of Masterbatch by Heat Coagulation" of Experimental Example 1-1, a rubber sheet was prepared in the same manner as above, except that the octyldithioesterified CNF prepared in Example 4 was used instead of the allyldithioesterified CNF, and strength properties were measured. Tc90 was 7.1 minutes.

[0066] The strength properties were also measured for Experimental Examples 1-4 and 1-5, and the stress at break and elongation were determined. The results are shown in Table 5 and Figure 3, comparing Experimental Example 1-1, in which the ester group is an allyl group, Experimental Example 1-4, in which the ester group is a butyl group, Experimental Example 1-5, in which the ester group is an octyl group, and Comparative Experimental Example 1-1, in which no CNF was added. Note that M30 indicates the tensile stress at 30% elongation, M100 indicates the tensile stress at 100% elongation, and M300 indicates the tensile stress at 300% elongation.

[0067] [Table 5]

[0068] (Consideration) Regardless of the substituent, the values ​​were superior to those of Comparative Experiment 1-1 in which no substituent was added, and almost no difference was observed in the change in stress due to the substituent.

[0069] (Evaluation of changes in coagulation method) (Experimental Example 1-6: Preparation of master batch by formic acid coagulation) Using the allyl dithioesterified CNF prepared in Example 1, the dithioesterified CNF, NR latex, and 14 mass% ammonia water were mixed as shown in the configuration of "Preparation of master batch by heat coagulation" in Experimental Example 1-1. While stirring the mixed slurry, a 2 mass% formic acid aqueous solution was dropped until the pH became 4. Furthermore, the precipitated rubber particles were collected by vacuum filtration and washed until neutral. After that, the mixture was dried at 70 ° C for 2 days, and then dried under reduced pressure to prepare an NR master batch. The sulfur content in the NR master batch was measured by the same procedure as in Example 1 <Measurement of sulfur content of xanthate-modified CNF>, and the result was 306.6 ppm. The obtained NR master batch was used to prepare a rubber sheet by the same procedure as in Experimental Example 1-1, and strength properties were measured. Tc90 was 7.6 minutes.

[0070] (Experimental Comparative Examples 1-3 and 1-4) In Experimental Example 1-6, a rubber sheet was produced from an NR master batch (Experimental Comparative Example 1-3) produced by the same procedure as in Experimental Example 1-6 except that dithioesterified CNF was not added, and an NR master batch (Experimental Comparative Example 1-4) produced by the same procedure as in Experimental Example 1-6 except that xanthate-modified CNF was used instead of dithioesterified CNF, and strength properties were measured. The sulfur content in the NR master batch of Experimental Comparative Example 1-3 was 45 ppm, and Tc90 was 7.8 minutes, and the sulfur content in the NR master batch of Experimental Comparative Example 1-4 was 49 ppm, and Tc90 was 8.1 minutes.

[0071] The results of measuring the sulfur content in each NR master batch for Experimental Example 1-6 and Comparative Experimental Examples 1-3 and 1-4 are shown in Table 6. The strength property measurements were also performed, and the results of determining the stress at break and elongation are also shown in Table 6, and a graph is shown in Figure 4. Note that M30 indicates the tensile stress at 30% elongation, M100 indicates the tensile stress at 100% elongation, and M300 indicates the tensile stress at 300% elongation.

[0072] [Table 6]

[0073] (Consideration) The master batch (Experimental Example 1-6) containing allyl dithioesterified CNF coagulated by adding formic acid showed a high sulfur content. In comparison, the xanthate-modified CNF (Experimental Comparative Example 1-4) coagulated by adding formic acid showed a low sulfur content almost equivalent to that of the non-added case (Experimental Comparative Example 1-3). This is thought to be because the -SCC- group of the xanthate-modified CNF was eliminated by formic acid, but the functional group was not eliminated from the dithioesterified CNF even when it was coagulated by adding formic acid. In addition, from the stress-strain curve in FIG. 4, it was confirmed that the strength improvement effect was higher in the dithioesterified CNF (Experimental Example 1-6) than in the xanthate-modified CNF (Experimental Comparative Example 1-4). This is thought to be because the functional group was not eliminated by formic acid, so the hydrophobicity was maintained high, improving the dispersibility in the rubber.

[0074] (Consider using it in combination with carbon black) (Experimental Example 1-7) In Experimental Example 1-1, when preparing a compound sheet from the NR master batch to which 5 phr of allyldithioesterified CNF was added, 20 phr of carbon black (manufactured by Tokai Carbon Co., Ltd.: SEAT 3: abbreviated as "CB" in the table) was also added, and a vulcanized rubber sheet was obtained in the same manner as in Experimental Example 1-1. Tc90 was 7.9 minutes. The measurement results of the stress at break and elongation are shown in Table 7 and Figure 5. Note that M30 indicates the tensile stress at 30% elongation, M100 indicates the tensile stress at 100% elongation, and M300 indicates the tensile stress at 300% elongation.

[0075] (Experimental Comparative Examples 1-5 and 1-6) In Experimental Example 1-7, a vulcanized rubber sheet was obtained by the same procedure except that dithioesterified CNF was not added and only 20 phr of carbon black was added when preparing the compound sheet (Experimental Comparative Example 1-5). Similarly, a vulcanized rubber sheet was obtained by the same procedure except that only 40 phr of carbon black was added (Experimental Comparative Example 1-6). The measurement results of the stress at break and elongation are shown in Table 7 and Figure 5.

[0076] [Table 7]

[0077] (Consideration) The stress was better in Experimental Example 1-7, which used 5 phr of dithioesterified CNF in combination, than in Experimental Comparative Example 1-5, which added only 20 phr of carbon black. In addition, Experimental Comparative Example 1-6, which added only 40 phr of carbon black, and Experimental Example 1-7, which used 5 phr of dithioesterified CNF and 20 phr of carbon black in combination, showed almost the same behavior in the stress-strain curve up to about 200% elongation. This shows that dithioesterified CNF exerts a synergistic effect with carbon black when added to a resin. This shows that it is possible to replace part of the carbon black with dithioesterified CNF and reduce the amount of carbon black added.

[0078] (Vulcanization acceleration effect) Table 8 shows the results of measuring the vulcanization time for the above experimental examples and comparative examples.

[0079] [Table 8]

[0080] (Consideration) In the dithioesterified CNF (Experimental Examples 1-1, 1-3, 1-4, 1-5, 1-7) coagulated by heating, the Tc90 value was smaller than that in the case where no formic acid was added (Experimental Comparative Example 1-1). This is thought to be due to the effect of accelerating vulcanization due to the influence of the dithioester group. In addition, in the dithioesterified CNF (Experimental Example 1-6) coagulated by adding formic acid, the Tc90 value was smaller than that in the xanthate-containing CNF (Experimental Comparative Example 1-4) coagulated by adding formic acid and the case where no formic acid was added (Experimental Comparative Example 1-3). This is thought to be due to the fact that, although the -SCC- group of the xanthate-containing CNF is eliminated by formic acid, the functional group is not eliminated even when the dithioesterified CNF is coagulated by adding formic acid, and thus the vulcanization accelerating effect was observed.

[0081] <2. Confirmation of the effect of enhancing the strength of TPE film by mixing with thermoplastic elastomer> (Experimental Example 2-1) Preparation of CNF composition To the allyl dithioesterified CNF aqueous suspension (dithioesterified CNF content 1% by mass, sulfur content 8.6% by mass) prepared in Example 1, 1,4-butanediol (manufactured by Tokyo Chemical Industry Co., Ltd.) was added as a redispersing agent after drying in an amount 10 times the mass ratio of the dithioesterified CNF, and 30 g of a mixture with a CNF concentration of 0.7% by mass and a polyol concentration of 7.0% by mass was prepared. This mixture was dried for 15 hours at 60 ° C. using a hot air dryer to obtain a dithioesterified CNF composition. The obtained dithioesterified CNF composition had a CNF solid content of 9.4% by mass, a water content of 5.8% by mass, and a 1,4-butanediol content of 84.8% by mass.

[0082] Preparation of DMF dispersion of dithioesterified CNF N,N'-dimethylformamide (DMF) (Kanto Chemical Co., Ltd.) was added to the dithioesterified CNF composition obtained above so that the solid concentration of dithioesterified CNF was 0.2 mass%, and the mixture was stirred and mixed at 10,000 rpm for 10 minutes using a rotary homogenizer (Nippon Seiki Seisakusho Co., Ltd., AM-7) to disperse the dithioesterified CNF in DMF. The composition of the DMF dispersion of allyl dithioesterified CNF is shown in Table 9.

[0083] [Table 9]

[0084] ·Mixing with TPE and film formation The DMF dispersion of allyl dithioesterified CNF obtained above was mixed with a thermoplastic elastomer (TPE) solution (T-78F manufactured by Dainichi Seikagaku Kogyo Co., Ltd.) so that the solid content of dithioesterified CNF was 1 part by mass (=1 phr) per 100 parts by mass of TPE, and a stirring and mixing process was performed for 15 minutes at 8000 rpm using a rotary homogenizer. This dithioesterified CNF mixed TPE solution was degassed for 3 minutes at 3000 rpm using a centrifuge (Avanti J-251 manufactured by Beckman Coulter Co., Ltd.). The degassed solution was cast on an OPP film (thickness 40 μm) with a thickness of 380 μm using a Baker type applicator (manufactured by Tester Sangyo Co., Ltd.), and dried for 5 minutes at 120 ° C. using a hot air dryer to produce a TPE film (250 mm × 200 mm) containing allyl dithioesterified CNF.

[0085] -TPE film thickness measurement The obtained TPE film was measured at six random locations (120 locations per 1 m × 1 m) using a thickness measuring instrument dial gauge 0.001 mm manufactured by Ozaki Manufacturing Co., Ltd. in accordance with JIS Z1702, and the average of the measured values ​​was taken as the thickness. The results are shown in Table 10.

[0086] Tensile strength measurement From the obtained TPE film, rectangular test pieces with a width of 20 mm and a length of 100 mm were punched out, and a tensile test (n=3) was performed using an autograph AG-500NX manufactured by Shimadzu Corporation under the conditions of a grip width of 20 mm and a tensile speed of 300 mm / min, and the tensile stress and elongation (= strain) were obtained from the results. The results are shown in Table 10 and Figure 6. Note that phr indicates the parts by mass (amount added) of CNF added relative to 100 parts by mass of TPE, M100 indicates the tensile stress at 100% elongation, and M300 indicates the tensile stress at 300% elongation.

[0087] (Evaluation of physical properties regarding differences in additive amounts) (Experimental Example 2-2: Increased amount added) In the preparation stage of the DMF dispersion of allyl dithioesterified CNF in Experimental Example 2-1, the solid content concentration of dithioesterified CNF was increased to 1 mass%, and the dithioesterified CNF was mixed with the DMF dispersion of dithioesterified CNF so that the solid content of dithioesterified CNF was 5 mass parts (= 5 phr) per 100 mass parts of TPE when mixed with the TPE solution. A TPE film containing dithioesterified CNF was prepared by the same procedure as in Experimental Example 2-1. The composition of the DMF dispersion of allyl dithioesterified CNF is shown in Table 9, and the strength measurement results are shown in Table 10 and Figure 6.

[0088] (Experimental Comparative Example 2-1: No dithioesterified CNF added) In the procedure of "Mixing with TPE and film formation" in Experimental Example 2-1, a film was produced using only the TPE solution without adding the DMF dispersion of dithioesterified CNF. The film thickness and tensile strength of the produced film were measured in the same manner as in Experimental Example 2-1. The results are shown in Table 10 and Figure 6.

[0089] (Experimental Comparative Example 2-2: Xanthate-treated CNF added) In the same manner as in the method of Experimental Example 2-1, 1,4-butanediol was added as a redispersant after drying to the xanthated CNF aqueous suspension (sulfur content 8.7% by mass) prepared in Example 1 so that the amount was 10 times that of the xanthated CNF, and 30 g of a mixture with a CNF concentration of 0.7% by mass and a polyol concentration of 7.0% by mass was prepared. This mixture was dried at 60 ° C. using a hot air dryer for 15 hours to obtain a CNF composition. The CNF solid content of the obtained composition was 9.7% by mass, the water content was 6.8% by mass, and the 1,4-butanediol content was 83.5% by mass. DMF was added to this CNF composition and a redispersion treatment was performed, but many aggregates were confirmed in the DMF after the redispersion treatment. This DMF dispersion was mixed with a TPE solution to form a film, and the strength of the film was measured. The results are shown in Table 10 and FIG. 6.

[0090] [Table 10]

[0091] The TPE film containing xanthate-modified CNF (Experimental Comparative Example 2-2) has lower thermal stability than allyldithioesterified CNF (Experimental Examples 2-1 and 2-2), and it is believed that the xanthate group was eliminated during drying when preparing the CNF composition, causing the CNF to aggregate. The aggregated CNF was not dispersed by redispersion treatment in DMF, and existed as aggregates when mixed with the TPE solution and formed into a film, which is thought to have resulted in the film elongation being smaller in Experimental Comparative Example 2-2 than in Experimental Examples 2-1 and 2-2.

[0092] <3. Confirmation of the strength enhancement effect by mixing with polypropylene> (Experimental Example 3-1) Preparation of CNF composition To the allyl dithioesterified CNF aqueous suspension (dithioesterified CNF content 1% by mass, sulfur content 8.6% by mass) prepared in Example 1, dipropylene glycol (manufactured by Nacalai Tesque) was added as a redispersing agent after drying in an amount 5 times the amount of dithioesterified CNF, and 30 g of a mixture with a CNF concentration of 0.7% by mass and a polyol concentration of 3.5% by mass was prepared. This mixture was dried at 60 ° C for 15 hours using a hot air dryer to obtain a dithioesterified CNF composition. The obtained dithioesterified CNF composition had a CNF solid content of 15.2% by mass, a water content of 5.8% by mass, and a dipropylene glycol content of 79.0% by mass.

[0093] Mixing with PP resin and preparing test pieces 1.0 g of the dithioesterified CNF composition obtained above was mixed with 15 g of polypropylene resin (Wintec WFX4M, manufactured by Japan Polypropylene Co., Ltd.) so that the solid content of allyl dithioesterified CNF was 1 part by mass (=1 phr) per 100 parts by mass of PP, and the mixture was kneaded at 180 ° C for 5 minutes using a small tabletop kneader (DSM Xplore MC15M, manufactured by Xplore Instruments) to obtain a kneaded resin. Then, a dumbbell test piece (JIS K 7162-1BA type) was produced using an injection molding machine for producing test pieces (DSM Xplore IM12M, manufactured by Xplore Instruments).

[0094] - Dumbbell test piece thickness measurement The thickness of the dumbbell test piece was measured at three points on the neck using a thickness measuring instrument dial gauge 0.001 mm manufactured by Ozaki Seisakusho Co., Ltd., and the average value was calculated. The results are shown in Table 11.

[0095] Tensile strength measurement Using an autograph AG-500NX manufactured by Shimadzu Corporation, tensile tests (n=3) were conducted under conditions of a gripping width of 55 mm and a tensile speed of 100 mm / min, and the tensile yield stress and breaking strain ("strain" in the figure = elongation) were obtained from the results. The results are shown in Table 11 and Figure 7. Note that phr indicates the parts by mass (amount) of CNF added relative to 100 parts by mass of PP.

[0096] (Experimental Comparative Example 3-1: Dithioesterified CNF not added) In the method of "Kneading into PP resin and preparation of test pieces" in Experimental Example 3-1, dumbbell test pieces were prepared using only PP without adding the dithioesterified CNF composition. The film thickness and tensile strength of the prepared test pieces were measured in the same manner as in Experimental Example 3-1. The results are shown in Table 11 and Figure 7.

[0097] (Experimental Comparative Example 3-2: Xanthated CNF) In the same manner as in the method of Experimental Example 3-1, dipropylene glycol was added as a redispersant after drying to the xanthated CNF aqueous suspension (sulfur content 8.7% by mass) prepared in Example 1 so that the amount was 5 times that of the xanthated CNF, and 30 g of a mixture with a CNF concentration of 0.7% by mass and a polyol concentration of 3.5% by mass was prepared. This mixture was dried at 60 ° C. for 15 hours using a hot air dryer to obtain a CNF composition. The CNF solid content of the obtained composition was 16.1% by mass, the water content was 6.2% by mass, and the dipropylene glycol content was 77.7% by mass. This CNF composition was added to PP resin and kneaded, but many aggregates were confirmed in the dumbbell test piece. The results of measuring the strength of this dumbbell test piece are shown in Table 11 and FIG. 7.

[0098] [Table 11]

[0099] (Consideration) The xanthate-modified CNF (Experimental Comparative Example 3-2) has lower thermal stability than the dithioesterified CNF (Experimental Example 3-1), and it is believed that the xanthate group was eliminated during drying when preparing the CNF composition, causing the CNF to aggregate. The aggregated CNF was not dispersed by kneading with the PP resin, and existed as aggregates in the PP resin, which is believed to have reduced the stress and elongation.

Claims

1. A cellulose nanofiber is a nanofiber having a cellulose skeleton, and has a dithioester group represented by the following formula (1) in place of any of the hydroxyl groups of cellulose. -OCSSR (1) (R is a hydrocarbon group having 1 to 12 carbon atoms)

2. 2. The dithioesterified cellulose nanofiber according to claim 1, wherein the degree of substitution, which is the average number of hydroxyl groups substituted with the dithioester group per glucose unit constituting the cellulose skeleton, is 0.1 or more and 0.4 or less, and the average fiber diameter is 3 nm or more and 250 nm or less.

3. A method for producing dithioesterified cellulose nanofibers, comprising adding a halogenated hydrocarbon to an aqueous suspension of xanthated cellulose nanofibers to react with the xanthate groups.

4. A resin composition comprising the dithioesterified cellulose nanofiber according to claim 1 or 2.

Citation Information

Patent Citations

  • Rubber composition for tire

    JP2005075856A

  • Rubber composition

    JP2014125607A

  • Modified nanocellulose, and resin composition containing modified nanocellulose

    JP2014148629A

  • Modified cellulose fiber

    JP2017053077A

  • Resin composition containing fine cellulose xanthate fibers

    WO2018235912A1